Digital Teaching Materials Based on Task-Based Language Learning (TBLL) with Environmental Education: Uses in Online Distance Learning - Syahrul Ramadhan; Atmazaki Atmazaki; Vivi Indriyani; Elfia Sukma (STAI Hubbulwathan Duri, 2022)
The COVID-19 pandemic has resulted in online distance learning. Even though today, science and technology have advanced, the teaching materials used by teachers are still dominated by printed and non-interactive teaching materials. The purpose of this research is to develop digital teaching materials based on Task Based Language Learning (TBLL) containing environmental education in Indonesian language learning in secondary schools. The research was conducted when learning was conducted online remotely. This type of research is Research Development (RD) with the Plomp development model (Preliminary Research, prototyping phase, assessment phase). The research instrument used a questionnaire, observation sheet, and tests. This study describes the results of product practicality based on field trials, with details of product practicality by teachers, product practicality by students, and student learning activities when using the product. Based on the results of the study, it shows that digital teaching materials based on Task Based Language Learning (TBLL) containing environmental education are categorized as very practical with a score of 93.54% based on teacher questionnaires and categorized as very practical with a score of 80.62% based on student questionnaires. In addition, while using digital teaching materials, students were very active with a score of 93.33%.